Molecular study of the effect of exposure to arsenic in the environment - Ponpat Tntarasunanont; Mathuros Ruchirawat; Jutamaad Satayavivad; Panida Navasumrit; Chongrak Polprasert; Preeda Pakpian; Suk, William A.; Center of Excellence on Environmental Health and Toxicology (Pathum Thani, Thailand : Asian Institute of Technology, 2012)
Inorganic arsenic is an environmental pollutant and known human carcinogen. Arsenic exposure in humans comes mainly from consumption of drinking water contaminated with inorganic arsenic . Arsenic effects different organ systems in human body with variety mode of actions. Several assumptions have been made on its possible mechanisms. Study of gene expression profiles in human cell is one of the models used to elucidate the effects of arsenic on specific target genes that might respond to the arsenic- induced genomic alterations. Microarray technology, which measures changes in gene expression at the transcriptional level, is a powerful tool for studying global cellular responses to toxicants. In this study, exposure to arsenic was conducted in vitro to determine genome -wide gene expression changes. Moreover, gene expression profiling was employed to explore the effects on human lymphoblast cell line and on cord blood lymphocyte from unexposed subject exposed to arsenic in vitro . Two cell types were used as model to investigate gene target possibly involved in arsenic induce genomic alterations that could be used as gene marker for arsenic exposure and to evaluate genes signature obtained from these studies as markers of early arsenic exposure. Besides, this study aimed to compare the results from in vitro studies with those from the previous study using cord blood lymphocytes from newborn babies exposed to arsenic in utero (Fry et al. 2007) . Lymphoblast cells were treated with 6 concentrations of NaAsO 2 from 0- 10 oM, which represented the low environmentally rele vant concentration to the high/non- cytotoxic levels. Cord blood lymphocytes were treated for 0, 1.0, 5.0 o M. After 24 hr RNA were isolated for gene expression study using Affymetrix HG -U133A Plus2 GeneChip Array. Results obtained from in vitro studies revealed a number of genes differentially expressed in a dose -response manner. These included disease/carcinogenesis related genes e.g stress responsive genes. There is also a common set of genes found in both cell types indicating the possibility of using lym phoblast cell line as a surrogate for lymphocyte. Among the set of genes found to be related to arsenic exposure in the previous study, some were also represented in this current study such as the EGR1 gene. Besides the studies on gene expression, the effects of arsenic exposure in utero on global LINE -1 and p53 promoter methylation were studied in cord blood obtained from 55 arsenic -exposed and 16 unexposed subjects. The global DNA methylation in arsenic exposed cord blood was not significantly different f rom that of the unexposed group whereas p53 promoter methylation level was slightly increased compared to the unexposed group. There was a significant correlation (p<0.05) between p53 promoter methylation and the level of arsenic accumulation in toenails or fingernails of the newborn babies. The in vitro exposure to arsenic and its effects on global LINE -1 methylation, 5MedC levels and p53 promoter methylation were conducted using lymphoblast cell line treated with NaAsO 2 at low dose, long duration (0- 1 oM, 2- 8 weeks ). There was a decrease in methylation level (as % of control). T he lowest methylation level was found at 8 wk of treatment (decreased by 13.1% as compared to the control) with 0.5 oM arsenite and at 6 wk (decreased by 12.9%) with 1 oM arsenite treatment. Similar results were found with 5MedC. There were statistical significant (p<0.01) at 0.5 and 1.0 o M of 6 wk for long- term treatment indicating high sensitivity of 5MedC detection. For specific gene (p53) mehtylation, there was significant increases in p53 methylation le vels at 4 wk of treatment (3.9, 3.5 folds for 0.5 and 1 oM treatment, respectively) then decreased. In conclusion, This study provides an important finding that arsenic could effect expression of a variety of genes involved in different pathways both in cord blood lymphocyte and lymphoblast cell line as well as providing the information that in utero arsenic exposure affected DNA methylation, particularly at the p53 promoter region, which may be linked to the mechanism of arsenic carcinogenesis and the observed increased incidence of cancer later in life
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Environmental Engineering and Management , Inter - University Program on Environmental Toxicology, Technology and Management
Thesis (Ph.D.) - Asian Institute of Technology - Chulabhorn Research Institute - Mahidol University, 2012
Keywords: Arsenic -- Environmental aspects